PET/Ag NW/PMMA transparent electromagnetic interference shielding films with high stability and flexibility. Issue 17 (21st April 2021) - Zhu, Xingzhong; Guo, Aoqi; Yan, Zhiyang; Qin, Feng; Xu, Juan; Ji, Yanda; Kan, Caixia
Abstract : A highly stable and flexible transparent electromagnetic interference shielding film is realized based on silver nanowire by integrating a polymer layer. Abstract : Flexible transparent electromagnetic interference (EMI) shielding materials in visual windows are essential for the innovation of optoelectronic devices. Herein, we demonstrate the fabrication of flexible EMI shielding films based on silver nanowires (Ag NWs) and polymethyl methacrylate (PMMA). The purified Ag NWs are uniform in size and morphology, with aspect ratio over 1000. The PET/Ag NW/PMMA flexible transparent conductive films (FTCFs) with a sandwich structure were obtained via Mayer-rod coating of the Ag NWs and spin-coating of the PMMA polymer on a polyethylene terephthalate (PET) substrate. The root mean square roughness value of PET/Ag NW/PMMA FTCFs could decrease from 21 nm to 4 nm due to the filling of PMMA in the interface among Ag NWs. The PET/Ag NW/PMMA FTCFs can achieve a sheet resistance of 21 Ω sq −1 at a transmittance of 95.6%, resulting in a high figure of merit of 447. Moreover, the composite films exhibit remarkable flexibility after 10 000 continuous bending cycles, as well as great stability in harsh environments of 80 °C/80% RH aging for 600 h. An EMI shielding effectiveness (SE) of 21.3 dB in combination with a high optical transmittance of 95.6% for the PET/Ag NW/PMMA FTCFs is sufficient to satisfy the requirement of commercial transparent EMI shielding applications. The absorption component of the SE was demonstrated to play a dominant role in the EMI shielding mechanism. The comprehensive performance (flexibility, stability, transparency and EMI shielding performance) makes the PET/Ag NW/PMMA FTCFs have great potential as a flexible transparent EMI shielding material in emerging flexible optoelectronic devices.